Jean Vigo - Temple, Michael, 1963- (French film directors., 2019)
'Jean Vigo is one of the legendary figures of world cinema, whose films 'L'Atalante' and 'Zéro de conduite' still inspire young audiences today. Film historian Michael Temple explores Vigo's intense career and asks why it has had such a long-lasting impact on film culture, not just in France, but also for generations of filmmakers, critics, and moviegoers around the world. Each film is examined under four headings:- social and political context- the making of the film, from conception to release-detailed analysis of narrative structure, main stylistic features and dominant themes- the reception of the film and its critical reputationAccessibly written, this will be essential reading for students, teachers, film enthusiasts and researchers, indeed for anyone who is interested in the cinema as a living art form' --Back cover.